"The machine does it!": Using convenience technologies to analyze care, reproductive labor, gender, and class in urban Morocco. Issue 2 (12th May 2021) - Dike, M. Ruth
Abstract : Convenience technologies have the ability to change the way people do reproductive labor, or labor associated with caregiving and domestic roles, in their households. Reproductive labor is disproportionately performed by women across the globe and underpins capitalism by creating cheap labor. This article investigates how convenience technology challenges and reinforces gender roles and socioeconomic class for urban Moroccans. Although experiences of "convenience" are highly variable, gender and socioeconomic class influence experiences of convenience technologies. Convenience technologies help urban Moroccan women by opening up reproductive labor to men and children but, simultaneously, hurt urban Moroccan women by devaluing their reproductive labor in relation to men's labor. Convenience technologies reinforce socioeconomic class by supporting a household's reputation and validating urban Moroccans' perceptions of themselves as citizens of a developed nation‐state. Besides expressing class, convenience technologies can contribute to a restructuring of women's position within the household. The article analyzes data collected during seventeen months of ethnographic fieldwork in Rabat‐Salé, Morocco, from 2018 to 2019. I conducted fifty‐three semistructured interviews with married middle‐ and lower‐class Moroccans in Moroccan Arabic, as well as extensive informal participant observation. I analyze the gendered and classed politics of reproductive labor in relation to convenience technologies.